Foregrounding the region. Issue 1 (2nd January 2017) - Paasi, Anssi; Metzger, Jonathan
ABSTRACT: Foregrounding the region. Regional Studies . This paper scrutinizes the everlasting but transforming significance of the concept of region for regional studies and social practice. After tracing the changing meanings of this category, it highlights one characteristic aspect of the progress of the academic conceptualizations of the region: recurrent iterations of critiques regarding various forms of essentialism and fetishism. The main focus then moves to the conceptualization of the region and the articulation of ideas about what regions substantially 'are' and 'do', and what makes the region a worthy object of attention (scholarly or otherwise). The paper concludes with a discussion about the implications of the perspective on regions developed in the article for the future of regional studies.